Automatic fire fighting robot with gas detection and alert system - Ashish Karpe; Pradip Targe; Aditya Shrikant Patil; Rushikesh Gange; Sheetal Waghchaware (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
Fire incidents in residential and industrial environments present serious risks to human safety and infrastructure, requiring rapid detection and effective mitigation systems. This study proposes the design and experimental evaluation of an automatic fire-fighting robot equipped with gas detection and real-time alert capabilities. The system is built around an ESP32 microcontroller and integrates a flame sensor for fire detection, an MQ-135 sensor for hazardous gas monitoring, and a GSM module for transmitting remote alert notifications. A motor-driven water pump is employed to autonomously suppress detected fires, while a dual-mode control mechanism enables both autonomous and manual operation. Experimental evaluations were conducted under controlled indoor conditions to assess system responsiveness and reliability. The results show that the robot is capable of detecting flame sources at distances of up to 80 cm, with an average response time of approximately 3.2 s from detection to fire suppression activation. The gas detection module successfully identified abnormal gas concentrations and triggered SMS alerts with a success rate exceeding 95%. The proposed robot demonstrates a low-cost, portable, and scalable solution for early fire detection and suppression in small-scale indoor environments such as homes, offices, and warehouses. By combining autonomous navigation, gas monitoring, and real-time communication within a single robotic platform, this work contributes to the advancement of intelligent fire-safety systems and IoT-based emergency response technologies.